The ROX coupler: Creation of a fixed iliac arteriovenous anastomosis for the treatment of uncontrolled systemic arterial hypertension, exploiting the physical properties of the arterial vasculature. Issue 5 (1st November 2014) - Foran, John P.; Jain, Ajay K.; Casserly, Ivan P.; Kandzari, David E.; Rocha‐Singh, Krishna J.; Witkowski, Adam; Katzen, Barry T.; Deaton, David; Balmforth, Peter; Sobotka, Paul A.
Abstract : Objectives: Uncontrolled hypertension, whether due to drug resistance or poor adherence and persistence, remains a problem in many patients. The ROX coupler is a novel technology designed to reduce arterial blood pressure consequent to the predicted physical effects of reducing vascular resistance and improving arterial compliance. This article describes the technical aspects of the device and implantation procedure, results from a preclinical study, patient selection criteria, and potential complications of this therapy for uncontrolled hypertension.Background: The coupler is a self‐expanding, stent‐like device that exploits the mechanical effects of the creation of a low‐resistance, high‐compliance venous segment to the central arterial tree, and can be implanted in a standard catheterization laboratory under fluoroscopic guidance.Methods: Preclinical studies were conducted in sheep with acute or chronic hypertension. The devices were implanted in the aorta for up to 12 months. The anastomoses were evaluated for patency, healing, conformation into the artery and vein, and complications.Results: Deployment of the anastomotic device in ovine aortas for up to 12 months showed optimal anastomotic patency in all animals with proper healing and conformation of the device into the artery and the vein. There was no significant residual mural thrombus and minimal to moderate intimal thickening at the vein outflow, consistent with expected arterialization.Conclusions: A novel arteriovenous coupler for percutaneous placement in the iliac vasculature is under clinical investigation as a potential treatment modality for selected patients with uncontrolled hypertension. Initial results from patients with uncontrolled hypertension are expected in Autumn 2014. © 2014 Wiley Periodicals, Inc.